University students and faculty have positive perceptions of open/ alternative resources and their utilization in a textbook replacement initiative - Delimont, Nicole; Turtle, Elizabeth C.; Bennett, Andrew; Adhikari, Koushik; Lindshield, Brian L. (My University, 2016)
The Kansas State University Open/Alternative Textbook Initiative provides grants to faculty members to replace textbooks with open/alternative educational resources (OAERs) that are available at no cost to students. Open educational resources are available for anyone to access, while alternative educational resources are not open. The objective of this study was to determine the perceptions towards OAERs and the initiative, of students enrolled in, and faculty members teaching, courses using OAERs. A survey was sent out to 2,074 students in 13 courses using the OAERs. A total of 524 (25.3%) students completed the survey and a faculty member from each of the 13 courses using OAERs was interviewed. Students rated the OAERs as good quality, preferred using them instead of buying textbooks for their courses, and agreed that they would like OAERs used in other courses. Faculty felt that student learning was somewhat better and it was somewhat easier to teach using OAERs than when they used the traditional textbooks. Nearly all faculty members preferred teaching with OAERs and planned to continue to do so after the funding period. These results, combined with the tremendous savings to students, support the continued funding of the initiative and similar approaches at other institutions. © 2016 N. Delimont et al.
Citation: Delimont, N., Turtle, E. C., Bennett, A., Adhikari, K., & Lindshield, B. L. L. (2016). University students and faculty have positive perceptions of open/ alternative resources and their utilization in a textbook replacement initiative. Research in Learning Technology, 24. doi:10.3402/rlt.v24.29920
Keywords: College; E-Textbook; Kansas State; Open Educational Resources; Open Textbook